Engineering of extracellular matrix from human iPSC-mesenchymal progenitors to enhance osteogenic capacity of human bone marrow stromal cells independent of their age - Hanetseder, Dominik; Levstek, Tina; Teuschl-Woller, Andreas Herbert; Frank, Julia Katharina; Schaedl, Barbara; Redl, Heinz; Marolt Presen, Darja (Frontiers in Bioengineering and Biotechnology, 2023)
Regeneration of bone defects is often limited due to compromised bone tissue physiology. Previous studies suggest that engineered extracellular matrices enhance the regenerative capacity of mesenchymal stromal cells. In this study, we used human-induced pluripotent stem cells, a scalable source of young mesenchymal progenitors (hiPSC-MPs), to generate extracellular matrix (iECM) and test its effects on the osteogenic capacity of human bone-marrow mesenchymal stromal cells (BMSCs). iECM was deposited as a layer on cell culture dishes and into three-dimensional (3D) silk-based spongy scaffolds. After decellularization, iECM maintained inherent structural proteins including collagens and laminin, and contained minimal residual DNA. Young adult and aged BMSCs cultured on the iECM layer in osteogenic medium exhibited a significant increase in proliferation, osteogenic marker expression, and mineralization as compared to tissue culture plastic. With BMSCs from aged donors, matrix mineralization was only detected when cultured on iECM, but not on tissue culture plastic. When cultured in 3D iECM/silk scaffolds, BMSCs exhibited significantly increased osteogenic gene expression levels and bone matrix deposition. iECM layer showed a similar enhancement of aged BMSC proliferation, osteogenic gene expression, and mineralization compared with ECM layers derived from young adult or aged BMSCs. However, iECM increased osteogenic differentiation and decreased adipocyte formation compared with single protein substrates including collagen and fibronectin. Together, our data suggest that the microenvironment comprised of iECM can enhance the osteogenic activity of BMSCs, providing a bioactive and scalable biomaterial strategy for enhancing bone regeneration in patients with delayed or failed bone healing.